Effects of Low Ground Pressure Vehicle Traffic on Tundra at Lonely, Alaska. - Abele,G; Brown,J; Brewer,M C; Atwood,D M (1977)
Traffic tests were conducted with two low pressure tire Rolligon-type vehicles and a small, tracked Nodwell with minimal load for 1, 5, and 10 vehicle passes on relatively dry tundra near Lonely, Alaska. The traffic impact was limited to compression of the vegetation and the organic mat and a maximum terrain surface depression of several cm, with no shearing or disaggregation of the mat. (Author)